2021
DOI: 10.1093/ndt/gfab263
|View full text |Cite
|
Sign up to set email alerts
|

Urinary biomarkers predict progression and adverse outcomes of acute kidney injury in critical illness

Abstract: Background Acute Kidney Injury (AKI) is common in hospitalized patients and is associated with high morbidity and mortality. The Dublin Acute Biomarker Group Evaluation (DAMAGE) Study is a prospective cohort study of critically ill patients (n = 717). We hypothesised that novel urinary biomarkers would predict progression of AKI and associated outcomes. Methods The primary (diagnostic) analysis assessed the ability of biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…On the other hand, elevations of IL-1β serum concentrations in human sepsis can be mild [ 174 ] or irregular [ 175 ], are dependent on the phase of septic state [ 176 ], and, in addition, the kidney has a role in IL-1β removal in sepsis as long as diuresis is preserved [ 177 ]. Recently, a study reported the association of urinary IL-18 protein concentrations with AKI progression in critically ill patients at the intensive care unit [ 178 ] and a meta-analysis of biomarkers in S-AKI reported a correlation of urinary IL-18 and the diagnosis of S-AKI [ 179 ].…”
Section: Inflammasome Components In Akimentioning
confidence: 99%
“…On the other hand, elevations of IL-1β serum concentrations in human sepsis can be mild [ 174 ] or irregular [ 175 ], are dependent on the phase of septic state [ 176 ], and, in addition, the kidney has a role in IL-1β removal in sepsis as long as diuresis is preserved [ 177 ]. Recently, a study reported the association of urinary IL-18 protein concentrations with AKI progression in critically ill patients at the intensive care unit [ 178 ] and a meta-analysis of biomarkers in S-AKI reported a correlation of urinary IL-18 and the diagnosis of S-AKI [ 179 ].…”
Section: Inflammasome Components In Akimentioning
confidence: 99%
“…Interestingly, that association was maintained in the adjusted model, similar to previously published data. 19 This study was not designed to confirm the clinical benefit of NGAL testing in optimizing management and outcomes following an AKI episode. However, as shown by the post-NGAL questionnaire, the use of that novel biomarker in clinics was globally appreciated by consultant nephrologists.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, that association was maintained in the adjusted model, similar to previously published data. 19 …”
Section: Discussionmentioning
confidence: 99%
“…The urinary panel consisted of NGAL, albumin, KIM-1, L-FABP, and cystatin C. Thirty-eight percent of the patients developed AKI, 215 (84%) during the first 48 h and 42 (16%) after 48 h but before seven days [ 117 ]. A secondary analysis of the DAMAGE study assessed 14 urinary biomarkers [ 118 ]. In the group of patients that presented AKI stage 1 or 2 within 48 h after ICU admission, eight biomarkers were associated with progression to worse AKI stages, KRT, or death in 7 days.…”
Section: Biomarker Panelmentioning
confidence: 99%